Nominals with zero suffixation in Anna Akhmatova's early poems - T.A. Korneyeva (Ученые записки Казанского университета: Серия Гуманитарные науки)
Zero suffixation in Anna Akhmatova’s poetic texts was studied. The textual analysis of A. Akhmatova’s early poems rich in nominals with various types of zero suffixation was performed. Comparison with her later poems was carried out. On the one hand, this approach shows A. Akhmatova’s desire to overcome the traditions of symbolism and her attempts to develop an original style. On the other hand, nominals with zero suffixation clearly prevailed in A. Akhmatova’s early poems as compared with the later works. Particular attention was paid to the role of nominals with zero suffixation in the poetic space organization of two poetry collections: “Evening” (‘Vecher’) and “Beads” (‘Chetki’). We considered lexical, word-building, syntagmatic, grammatical, stylistic, tropeic, and other features of derivatives of zero suffixes in these poetry collections. It was revealed that nominals with zero suffixation were mainly used as a means of concentration of meanings and embodiment of the special drama of the poet’s lyrical monologue. The results of the research are important for expanding the knowledge on the text-forming function of word formation and, in particular, nominals with zero suffixation.